When Is Parenteral Nutrition Appropriate?. (17th February 2017) - Worthington, Patricia; Balint, Jane; Bechtold, Matthew; Bingham, Angela; Chan, Lingtak‐Neander; Durfee, Sharon; Jevenn, Andrea K.; Malone, Ainsley; Mascarenhas, Maria; Robinson, Daniel T.; Holcombe, Beverly
Abstract : Parenteral nutrition (PN) represents one of the most notable achievements of modern medicine, serving as a therapeutic modality for all age groups across the healthcare continuum. PN offers a life‐sustaining option when intestinal failure prevents adequate oral or enteral nutrition. However, providing nutrients by vein is an expensive form of nutrition support, and serious adverse events can occur. In an effort to provide clinical guidance regarding PN therapy, the Board of Directors of the American Society for Parenteral and Enteral Nutrition (ASPEN) convened a task force to develop consensus recommendations regarding appropriate PN use. The recommendations contained in this document aim to delineate appropriate PN use and promote clinical benefits while minimizing the risks associated with the therapy. These consensus recommendations build on previous ASPEN clinical guidelines and consensus recommendations for PN safety. They are intended to guide evidence‐based decisions regarding appropriate PN use for organizations and individual professionals, including physicians, nurses, dietitians, pharmacists, and other clinicians involved in providing PN. They not only support decisions related to initiating and managing PN but also serve as a guide for developing quality monitoring tools for PN and for identifying areas for further research. Finally, the recommendations contained within the document are also designed to inform decisions made by additional stakeholders, such as policy makers and third‐party payers, by providing current perspectives regarding the use of PN in a variety of healthcare settings.